Professional Ethics of Marriage Officiants from a Legal Perspective: A Juridical-Empirical Study of Indications of Gratification and Conflicts of Interest in Marriage Services - Asjach, Achmad Shiva’ul Haq (Jurnal Indonesia Sosial Sains, 2026)
Public services, including marriage registration, require integrity and professional ethics from state officials to prevent malpractices such as gratification and conflicts of interest. However, empirical reality often shows a gap between legal norms and field practices. This research aims to analyze the professional ethics of marriage registrars from a legal perspective and to examine indications of gratification practices and conflicts of interest in marriage services. The research employs a juridical-empirical method with statutory and sociological approaches, using literature review and interviews with informants at an anonymized Office of Religious Affairs. The findings reveal a gap between ethical norms and practices in the field, indicated by informal giving from the public to registrars and the role of intermediaries in handling administrative procedures, which may give rise to conflicts of interest. These practices are influenced by cultural factors, limited transparency, and insufficient public understanding of official procedures. The study concludes that strengthening oversight, enhancing service transparency, and improving public education are essential to achieving integrity and accountability in marriage services.